Judul Pengaruh Media Audio Visual Untuk Meningkatkan Keterampilan Dribling dan Passing Pada Permainan Futsal di Club Petropali - Abid Raihan Pirdau; Taheri Akhbar; Bambang Hermansah (Student Research Journal, 2024)
The problem in this study is whether there is an increase in Dribbling and Passing Skills in Futsal Games at the Petropali Club. This type of research is a quantitative approach, using Numerical Design. The population in this study were 15 active athletes of the Petropali Club. Data collection techniques used Pretest and Posttest calculations. The results of the research and data analysis, it can be concluded that there is a significant influence between Audio Visual training on improving Futsal results in Petropali Futsal Club Athletes, with Futsal passing results in the pretest having an average of 7.07 with the category "less" while the average result in the posttest 11.20, while the Dribbling pretest result was 4.6580 with the category "good" while the average result in the posttest was 3.4327 with the category "less". These results prove that there is an increase after being given treatment with Audio Visual training for 6 meetings with an increase in the percentage of passing of 4.13, while the percentage of Dribbling was 1.7267.